Effect of Input Angle, Dimension Ratio-Mechanism Link to the Output, Transmission Angle and Motion Characteristic - Sutikno, Endi; Ariseno, Agustinus (Jurnal Rekayasa Mesin, 2011)
In the previous study, the design of a four bar linkage mechanism had been analyzed by using a constant length dimension of link. The relationship between degree inputs to degree output was generated by using mathematic model of generator function. In this study, variation of length dimension of link was investigated to find the characteristic the output motion of four bar linkage mechanism. The input degree, ratio of link number 2 (R2), ratio of link number 3 (R3) and ratio of link number 4 (R4) is chosen as independent variable. It can be described by using output degree, transmission degree, coupler degree and possibility of the motion path. The result shows that the increasing rate of output degree number 4 on the R2 variation is larger than increasing rate of output degree number 4 on the variation of R3 and R4. Variation of R2 generated one working domain on the input degree number 2 to output degree number 4. The coupler degree on R2 variation produced a larger domain than it’s produced by R3 and R4 variation. In addition, the transmission degree for all control variables of R2, R3 and R4 obtain a polynomial curve tends to resemble as parabolic curve. For increasing of R3 and R4, the curve is transformed from two domains into one domain. Moreover, for increasing of R2, the curve is transformed in the opposite way.Keywords: lingkage, input angle, output angle, transmition angle, dimension ratio